2009
DOI: 10.1007/s00415-009-5367-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of the muscle volume analyzer to evaluate enzyme replacement therapy in late-onset Pompe disease

Abstract: The muscle volume analyzer (MVA) can predict limb muscle weight based on bioelectric impedance analysis, whereas the conventional handheld dynamometer (HHD) measures muscle strength. In this study, a 26-year-old female on invasive ventilation due to late-onset Pompe disease was treated with enzyme replacement therapy (ERT) for 12 months. MVA measurements demonstrated time-dependent improvement from the baseline compared to HHD measurements, showing remarkably fluctuating muscle strength. Thus, the MVA can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
7
0
1
Order By: Relevance
“…Similar variable improvements in strength were seen in six patients when the HHD tool was used to measure muscle strength (Sugai et al 2010;van Capelle et al 2008van Capelle et al , 2010 (Fig. 4b).…”
Section: Gross Motor Functionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similar variable improvements in strength were seen in six patients when the HHD tool was used to measure muscle strength (Sugai et al 2010;van Capelle et al 2008van Capelle et al , 2010 (Fig. 4b).…”
Section: Gross Motor Functionmentioning
confidence: 61%
“…Muscle functioning appears to improve with use of alglucosidase alfa, again with the largest improvements seen in the first 6 to 12 months of treatment. Improvements in gastrointestinal function and fatigue may also occur with the use of ERT (Bernstein et al 2010;Sugai et al 2010). The heterogeneity in the severity of symptoms between patients at baseline and the differences in the extent of treatment effect makes it difficult to determine which patients will do better than others.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recombinant GAA enzyme does not effectively cross the blood–brain-barrier where the protein may influence CNS GAA deficiency (Kikuchi et al, 1998; Raben et al, 2003). Accordingly, while intravenous GAA delivery can target cardiac and skeletal muscle (Levine et al, 2008; Sugai et al, 2010), it will not effectively mitigate CNS glycogen accumulation (Byrne et al, 2011b). This point is highlighted by our recent case study report in which a Pompe infant which had received enzyme replacement therapy showed considerable glycogen accumulation in the spinal cord on post-mortem examination (DeRuisseau et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest that ERT is more beneficial if started early in the course of disease [8,10,13,15], there were also a number of studies assessing the effects of ERT specifically in more severely affected patients. Eleven studies (36 patients) focused on patients who were invasively ventilated, required ventilation during part of the day or had an FVC in a supine position below 30%, and/or were fully wheelchair dependent or able to walk <40 m [28,30,[38][39][40][41][42][43][44][45][46]. These studies indicate that respiratory function and muscle strength can also improve/stabilize in these patients.…”
Section: Severely Affected Patientsmentioning
confidence: 99%